1991
DOI: 10.1099/00221287-137-7-1471
|View full text |Cite
|
Sign up to set email alerts
|

Growth kinetics of Agaricus bisporus mycelium on solid substrate (mushroom compost)

Abstract: Growth of Agaricus bisporus was studied on sterile compost and on sterile compost pre-grown with the thermophilic fungus Scytalidium thermophilum. Early growth was characterized by depressed, slowly growing hyphae. The mycelial radius extended exponentially in this stage. Mycelium on sterile compost switched to a fluffy growth type of radially orientated hyphae that extended at a linear rate, K,, of 5mmd-I. On compost pre-grown with S. thermophilum, early growth continued up to 30 mm, then extension became lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 18 publications
1
15
0
1
Order By: Relevance
“…For otherwise, with the proposed equation the dikaryotic strains showed λ values on wheat strain between 1.26 to 20.11 h and with the Gompertz model ranged from 1.82 to 28 h (Table 6). These results are similar to other authors using different math models, Straatsma et al (1991) reported λ values for A. bisporus since 0.46 to 0.71 h by using logistic functions. The lag phase (λ) indicates the capacity of the strain to adapt to new environmental condition (Chatterjee et al, 2015), in relation with this the hybrid PO 5 xLC 2 presented the shorter lag time (λ), hence this strain can get to the exponential phase faster to the other strains even to the parental strain.…”
Section: Mycelial Growth Kinetics Of Dikaryotic Strains On Mea and Whsupporting
confidence: 82%
See 1 more Smart Citation
“…For otherwise, with the proposed equation the dikaryotic strains showed λ values on wheat strain between 1.26 to 20.11 h and with the Gompertz model ranged from 1.82 to 28 h (Table 6). These results are similar to other authors using different math models, Straatsma et al (1991) reported λ values for A. bisporus since 0.46 to 0.71 h by using logistic functions. The lag phase (λ) indicates the capacity of the strain to adapt to new environmental condition (Chatterjee et al, 2015), in relation with this the hybrid PO 5 xLC 2 presented the shorter lag time (λ), hence this strain can get to the exponential phase faster to the other strains even to the parental strain.…”
Section: Mycelial Growth Kinetics Of Dikaryotic Strains On Mea and Whsupporting
confidence: 82%
“…The different values of instantaneous velocity with these authors depend of the different culture media used to the mycelium growth. Figure 1 shows the increasing growth speed on MEA, due to the rich content of nutrients in the culture media, Straatsma et al (1991) indicates that nutritive medium …”
Section: Formation Of Inter-generic Strainsmentioning
confidence: 99%
“…Among these microorganisms, thermophilic fungi appear to be important for compost selectivity. Torula thermophila and Humicola grisea var thermoidea (synonyms of Scytalidium thermophilum) (Straatsma et al, 1991), have been shown to be the most abundant thermophilic fungi in mushroom compost (Ross and Harris, 1983;Straatsma et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…thermoidea, = H. insolens; Straatsma and Samson 1993) (Ross and Harris 1983b). A positive correlation existed between its density in compost and mushroom yield (Straatsma et al 1989) and it strongly stimulated the rate of extension growth of mushroom mycelium in vitro (Straatsma et al 1991. Scytalidium thermophilum is present in straw and horse droppings and is common in selfheating substrates (Straatsma et al 1994a).…”
Section: Microbiologymentioning
confidence: 97%